Supply chain management: um estudo m survey no pólo farmacêutico goiano - Borges, Sônia Mara Silva (2009)
The Supply Chain Management has been showed up as an increasing model adopt in the business world, being ahead of the organizations necessities to rethink their strategies toward the organizations frontiers. Improvement on the proceedings involved on the network links of supllies has the sinergetic effect on the global network performance. This research describes the management performance of the supllies network of drugstore industry from Goiás pole, from the business process: to plan, to suplly, to produce, to distribute and to come back sanctioned by the SCOR model (Supply Chain Operations Reference) The work method consisted of a literature review, covered the contributions about the reference model, allowing that we tested five hypothesis linked on the studied process. To test the hypothesis, a survey was conducted, sent to the all eighteen drugstore industries of the pole, and had an answer tax of fifty six per cent. The results gained, treated by describes statistics techniques suggest that the drugstore industry, don t matter the charge, mainly have the supllies network based in system produced pushed, with little integration between the inter-industries process (links of the network), as the provision side as the demand side.